STUDTY OF LONGITUDINAL STABILITY OF HELICAL HONE WITH HELICAL GROOVES - SHCHERBYNA, KYRYL; MAZHARA, VITALII; TORCHILOV, DANYLO; ZAIKA, ANDRII; MASLIANIKOV, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Improving the functional characteristics of machines, mechanisms and equipment widely used in modern engineering is possible by optimising finishing operations. One of the key factors that determines the efficiency of hydraulic machines and fuel systems of internal combustion engines is the quality of the parts of the control equipment. The main quality indicators are surface roughness and the presence of macro-irregularities. The achievement of the required quality parameters in the finishing stages of bore machining depends on the application of the honing process.The flexibility of the honing process is determined by the ability to adapt the machining modes to the existing geometric deviations. At the same time, one of the main disadvantages of traditional honing heads is their design, which is based on the use of an expansion wedge. This element allows the radial dimension to be adjusted and a specific pressure to be applied to the surface being machined. However, the adjustment of the radial dimension takes place in the zone of small displacements, which causes the expansion wedge to operate in the mode of transition from static to kinetic friction.The paper analyses the process of deformation of an elastic screw hone in the axial direction, taking into account various designs of a closed screw groove. On the basis of the research conducted, mathematical models of the bending deformation of the geometric axis of the elastic screw hone under the action of static loads are developed, taking into account the additional resistance caused by elastic deformations. In order to verify the obtained mathematical models, a solid model was studied using the finite element method in the SolidWorks simulation environment. As a result, the optimal design of the elastic screw shank was determined.
Keywords: honing head; elastic screw hone; radial dimensional control system; elastic deformation; elastic deformable shell; small displacement zone